Pulsed field ablation in patients with complex consecutive atrial tachycardia in conjunction with ultra‐high density mapping: Proof of concept. (9th November 2022) - Gunawardene, Melanie A.; Schaeffer, Benjamin N.; Jularic, Mario; Eickholt, Christian; Akbulak, Ruken Ö.; Hedenus, Katja; Wahedi, Rahin; Anwar, Omar; Gessler, Nele; Hartmann, Jens; Willems, Stephan
Abstract: Introduction: Catheter‐ablation (CA) of consecutive left atrial tachycardias (LAT) can be challenging. Pulsed field ablation (PFA) yields a novel nonthermal CA technology for treatment of atrial fibrillation (AF). There is no data regarding PFA of LAT. This study sought to investigate PFA of consecutive LAT following prior CA of AF. Methods: Consecutive patients with LAT underwent ultrahigh‐density (UHDx) mapping. Subsequent to identification of the AT mechanism, PFA was performed at the assumed critical sites for LAT maintenance. Continuous ablation lines were performed if required and evaluated with pre‐ and post‐PFA HDx‐mapping. Results: Fifteen patients (age 70 ± 10, male 73%) who underwent 3.6 ± 2 prior AF‐CA procedures were included. The total mean procedure and fluoroscopy times were 141 ± 43 and 18 ± 10 min, respectively. All 19 of 19 (100%) LAT were successfully ablated with PFA. Two AT located at the right atria required RF‐ablation. LAT were identified as localized reentry ( n = 1) and macro‐reentry LAT ( n = 18) and targeted with PFA. All LAT terminated with PFA either to sinus rhythm (9/15) or a secondary AT (6/15 and subsequently to SR); 63% (12/19) terminated with the first PFA‐application. All lines (13 roof, 11 anterior, 1 mitral) were blocked. LA‐posterior‐wall isolation (LAPWI) was successfully achieved when performed (10/10). AF/AT free survival was 80% (12/15) after 153 [88–207] days of follow‐up. No procedure‐related complications occurred. Conclusion: PFA of consecutive LAT is feasible and safe. Successful creation of ablation lines and LAPWI can be achieved in a short time. PFA may offer the opportunity for effective ablation of atrial arrhythmias beyond AF.